Maternal and Cord Serum Cytokine Changes with Continuous and Intermittent Labor Epidural Analgesia: A Randomized Study - Venkat R. Mantha; Manuel C. Vallejo; Vimala Ramesh; Bobby L. Jones; Sivam Ramanathan (The Scientific World Journal)
Background. Maternal fever during labor epidural analgesia (LEA) may cause increased maternal and cord serum inflammatory cytokines. We report the effects of intermittent and continuous LEA on these cytokines. Methods. Ninety-two women were randomly assigned to continuous (CLEA) or intermittent (ILEA) groups, 46 in each. Maternal temperature was checked and blood drawn at epidural insertion (baseline) and four-hourly until 4 h postpartum (4 PP). Cord blood was drawn after placental delivery. Interleukin-1β (IL-1β), interleukin-6 (IL-6), interleukin-8 (IL-8), granulocyte macrophage-colony stimulating factor (GM-CSF), and tumor necrosis factor-α (TNF-α) were measured and analyzed according to group randomization, and then combined and reanalyzed as febrile (temperature ≥38°C) or afebrile groups. Results. Significant intragroup changes from baseline were noted in some groups. Data are pg/mL, median (Q1/Q3). IL-6 rose at all time points in all groups. CLEA: baseline: 18.5 (12.5/31.1), 4 h: 80.0 (46.3/110.8), 8 h: 171.9 (145.3/234.3), and 4 PP: 81 (55.7/137.4). ILEA: baseline: 15.7 (10.2/27.1), 4 h: 68.2 (33.3/95.0), 8 h: 125.0 (86.3/195.0), and 4 PP: 70.2 (54.8/103.6). Febrile group: baseline: 21.6 (13.8/40.9), 4 h: 83.9 (47.5/120.8), 8 h: 186.7 (149.6/349.9), and 4 PP: 105.8 (65.7/158.8). Afebrile group: baseline: 10.9 (2.1/17.4), 4 h: 38.2 (15.0/68.2), 8 h: 93.8 (57.1/135.7), and 4 PP: 52.9 (25.1/78). IL-8 rose at all time points in CLEA: baseline: 2.68 (0.0/4.3), 4 h: 3.7 (0.0/6.5), 8 h: 6.0 (3.3/9.6), 4 PP: 5.6 (0.8/8.0), and afebrile group baseline: 2.5 (0.0/4.7), 4 h: 3.3 (0.0/6.2), 8 h: 5.3 (1.9/9.8), and 4 PP: 4.7 (0.0/7.6). It fell at 4 PP in febrile group: baseline: 4.1 (0.0/6.4), 4 h: 3.8 (0.0/6.5), 8 h: 5.2 (2.5/8.0), and 4 PP: 2.9 (0.0/4.0). GM-CSF increased at 8 h and decreased at 4 PP in ILEA baseline: 2.73 (0.0/7.2), 4 h: 2.73 (0.0/7.9), 8 h: 3.9 (2.7/11.5), and 4 PP: 2.0 (0.0/7.2). It increased at 4 h and 8 h and decreased at 4 PP in febrile group: baseline: 2.6 (0.0/4.2), 4 h: 3.2 (2.1/7.0), 8 h: 4.0 (3.2/12.3), and 4 PP: 2.4 (1.7/12.6). There were no intergroup cytokine changes in maternal or cord serum in CLEA versus ILEA or febrile versus afebrile groups. Conclusions. Some cytokines, especially IL-6, rise physiologically during labor epidural analgesia.